Design of a haptic device for presenting pressure and skin stretching stimuli to the palm - Kojima, Mayuka; Yoshimoto, Shunsuke; Yamamoto, Akio (Frontiers in Mechanical Engineering, 2024)
This paper discusses the design of a two-degree-of-freedom (2-DOF) pseudo-force presentation device for a palm. The device was designed to present pressure stimulation to a palm to invoke a pseudo-force sensation. In addition, the stimulator can rotate to invoke a pseudo-torque sensation through tangential skin stretch in the proximal/distal direction. Whereas the previous devices used for pseudo-force presentation on a palm utilized voice coil motors (VCM) to generate pressure, the developed device uses a DC gear motor, cam, and lever, which comprise a series elastic actuator (SEA). Although the mechanism’s response is slower than the VCM-based device’s, it can realize lower power consumption when generating constant force. The paper discusses the design requirement to provide sufficient pseudo-force sensation. Then, a prototype device was evaluated, which satisfied the requirements regarding size, weight, force, and stroke. The device was utilized in a human-subject experiment to investigate the effect of tangential skin stretch along the proximal/distal direction on a palm. The results showed that the stimulation can invoke the feeling of rotation, or pseudo-torque sensation.